(untitled) (American Journal of Pedagogical and Educational Research, 2024)
This article presents the scientific basis for the development of students’ professional competencies based on an integrative approach. The concept of professional competence is explained in detail using the definitions of this concept by Uzbek and foreign scholars. The analysis fully justifies the need to use the integration of mathematics, computer science and physics in the development of students’ professional competencies.